(untitled) (Diversity Research: Journal of Analysis and Trends, 2025)
This paper evaluates why and how drying matters in producing coal-dust briquettes. We compare common drying routes—natural air/sun drying, warm-air convective drying (80– 120 °C), low-temperature vacuum drying, and microwave/infrared options—with respect to moisture removal rate, energy use, and effects on briquette quality. Results indicate that reducing feed moisture to a controlled target (typically 6–12%, depending on coal rank and binder) increases green and cured strength, lowers cracking during handling, and improves combustion efficiency. Proper drying also reduces the release of toxic gases during use by decreasing incomplete combustion and volatile carry-over associated with excess moisture. However, over drying can raise dusting and binder demand; thus, process control (inlet temperature, residence time, airflow) is critical. Overall, optimized drying is a key lever for safer, cleaner, and more durable coal-dust briquettes